Contaminantes emergentes e perfil de susceptibilidade de bactérias a antibacterianos em microbacia do rio Branco, Roraima, extremo norte do Brasil - Farias, Leovergildo Rodrigues (2022)
Surface waters are the main receptors of emerging contaminants and antibacterial-resistant bacteria because they receive urban, hospital and industrial sewage, surface runoff, as well as the drainage system, easily becoming a means of spreading diseases, causing impacts to health and the environment. New analytical techniques have made it possible to investigate the occurrence of emerging contaminants, such as caffeine and amoxicillin, in addition to the possibility of evaluating the susceptibility profile of bacteria to antibacterials, as well as the identification of these bacteria. Studies like these are still scarce in Brazil, especially in the Amazon region. Therefore, the objective of this research, a pioneer in the region, was to investigate the occurrence of the emerging contaminants caffeine and amoxicillin and to evaluate the susceptibility profile of bacteria to antibacterials in the Rio Branco watershed, Roraima, in the extreme north of the Amazon. To this end, High Efficiency Liquid Chromatography with ultraviolet detector (HPLC-UVDAD) was used to identify caffeine and amoxicillin; the agar diffusion method was used to evaluate the susceptibility profile of bacteria and the Matrix Assisted Laser Desorption/Ionization Time of Flight Mass Spectrocopy (MALDI-TOF/MS) method, as well as Near Infrared Spectroscopy (NIR) to identify resistant bacteria. The results of this study, are distributed in three articles that compose this thesis, in which, in general, they demonstrated the presence of caffeine, considered an indicator of contamination by sewage, and amoxicillin, an indicator of recalcitrant substances, in the Rio Branco watershed, with caffeine being detected more frequently. The results also revealed the presence of resistant bacteria, including to amoxicillin, in some of the studied points, being identified the presence of bacteria that cause waterborne diseases. In this study, it was evident that NIR spectroscopy, a fast, accurate and non-invasive technique, allowed the identification of bacterial isolates in surface water samples, as well as grouping them according to Gram type. These results point to the need for further studies with the objectives proposed here, monitoring emerging contaminants, as well as evaluating the presence of antimicrobial resistant microorganisms in aquatic environments, in order to contribute to environmental sustainability, including the health of the population.